The effect of of trend and halal life awareness on halal fashion product selection preferences - Ariza Qanita; Rohmatul Farohah Kholison; Mohammad Khoiruzi Afiq (Journal of Halal Product and Research (JHPR), 2022)
This study aims to determine the effect of trends and halal life awareness on consumer preferences in choosing halal fashion products. The method used in this research is quantitative with multiple linear regression analysis. The research respondents consisted of 116 students in UIN Sunan Ampel Surabaya who were taken by random sampling technique. The result of the study show that trend and halal life awareness have a significant effect on consumer preferences with the equation model Y= 6,279 + 1,097 + 1,358. The higher influence is halal life awareness with a regression coefficient of 1,359 compared to a trend of 1,097. These results indicate that public awareness about halal fashion product is quite good and even affects their consumption decisions. Public awareness about halal product can be a very potential opportunity for the development of the halal industry market in Indonesia especially in the fashion sector.